Selective hydrogenation of naphthols to tetralones over supported palladium catalysts in supercritical carbon dioxide solvent - Mine, Eiichi; Hiyoshi, Norihito; Sato, Osamu; Rode, Chandrashekhar V.; Shirai, Masayuki (Chemistry Letters, 2006)
Naphthols were selectively hydrogenated to the corresponding tetralones over supported palladium metal catalysts in super-critical carbon dioxide solvent.

Stereoselective hydrogenation of tert-butylphenols over charcoal-supported rhodium catalyst in supercritical carbon dioxide solvent - Hiyoshi, Norihito; Rode, Chandrashekhar V.; Sato, Osamu; Tetsuka, Hiroyuki; Shirai, Masayuki (Journal of Catalysis, 2007)
Hydrogenation of 2-, 3-, and 4-tert-butylphenols was studied over a charcoal- supported rhodium catalyst in supercritical carbon dioxide (scCO(2)) solvent, and the results were compared with those in organic solvents. In the hydrogenation of 4-tert-butylphenol, a higher cis ratio for 4-tert-butylcyclohexanol (0.79) was obtained in scCO(2) (10 MPa) than in 2-propanol (0.70) and cyclohexane (0.64) under similar conditions of hydrogen pressure (2 MPa) and temperature (313 K). In the case of 2-tert-butylphenol, the cis ratio for 2-tert-butylcyclohexanol was as high as 0.95 in both scCO(2) and 2-propanol (hydrogen pressure, 2 MPa; reaction temperature, 313 K). In the case of hydrogenation of 3-tert-butylphenol, the cis ratio decreased with the progression of consecutive hydrogenation of 3-tert-butylcyclohexanone intermediate. In addition, the stereoselectivity to cis-tert-butylcyclohexanols in scCO(2) was improved in the presence of hydrochloric acid. It was found that the protons of hydrochloric acid accelerated the hydrogenation of the intermediates, tert-butylcyclohexanones, to the corresponding cis-tert-butylcyclohexanols. The hydrogenation mechanism of tert-butylphenols, particularly the enhanced selectivity to cis-tert-butylcyclohexanols in scCO(2), is postulated based on the observed reaction profiles. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: charcoal-supported rhodium catalyst; stereoselective hydrogenation; supercritical carbon dioxide solvent; tert-butylcyclohexanol

Synthesis of hybrid 1,2,3-triazolo-delta-lactams/lactones using Huisgen [3+2] cycloaddition `click-chemistry' in water - Kumar, Indresh; Rana, Sravendra; Cho, Jae Whan; Rode, Chandrashekhar V. (Tetrahedron-Asymmetry, 2010)
The synthesis of a new class of hybrid 1,2,3-triazozlo-delta-lactams/lactones has been achieved using the Huisgen [3+2] dipolar cycloaddition `click-chemistry' reaction of various organic azides with an activated alkyne in water, followed by cyclization. (C) 2010 Elsevier Ltd. All rights reserved.

Selectivity tailoring in liquid phase oxidation over MWNT-Mn3O4 nanocomposite catalysts - Biswal, Mandakini; Dhas, Vivek V.; Mate, Vivek R.; Banerjee, Abhik; Pachfule, Pradip; Agrawal, Kanika L.; Ogale, Satishchandra B.; Rode, Chandrashekhar V. (Journal of Physical Chemistry C, 2011)
Highly selective multiwalled nanotubes (MWNT)-Mn3O4 nano-composite catalyst was designed for liquid phase oxidation of p-cresol, which gave highest selectivity of 90% to the first step oxidation product, p-hydroxy benzyl alcohol. Mn3O4 nanoparticles and MWNT-Mn3O4 nanocomposites were synthesized by coprecipitation route using mixed precursors under controlled conditions. The phase purity of Mn3O4 and the formation of MWNT-Mn3O4 nanocomposites were confirmed by X-ray diffraction, Raman spectroscopy, and X-ray photoelectron spectroscopy. High-resolution transmission electron microscopy revealed the selective exposure of (101) and (001) planes of Mn3O4 nanoparticles in the MWNT-Mn3O4 composite, while lowering in oxidizing capacity of MWNT-Mn3O4 nanocomposite confirmed by cyclic voltametry was due to incorporation of electron rich MWNT. Thus, selectivity tuning of the new material (MWNT-Mn3O4 nanocomposite) was found to be due to alteration in both geometric as well as electronic properties. A plausible reaction pathway also has been proposed involving the predominant role of nucleophilic lattice oxygen (O2-) species due to exposure of particular crystal planes giving highest selectivity to p-hydroxy benzyl alcohol.

Selectivity tuning options in hydrogenation of m-chloronitrobenzene to m-chloroaniline over mono- and bimetallic supported Pt catalysts - Mane, Rasika B.; Potdar, Aparna S.; Nadgeri, Jayprakash M.; Biradar, Narayan S.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2012)
Supported monometallic (Pt, Ni,) and bimetallic (Ni-Pt) catalysts were prepared for the selective liquid phase hydrogenation of m-chlronitrobenzene to m-chloroaniline (m-CAN). It was found that the use of sodium carbonate as an additive substantially reduced the extent of dehydrohalogenation in the case of monometallic, 1% Pt/C catalyst, to give the highest selectivity of 96% to m-CAN. Ni-Pt bimetallic catalyst although showed almost complete selectivity (>99%) to m-chloroaniline; its activity was several fold lower than that of 1% Pt/C Na2CO3 system. However, compared with Ni monometallic catalyst, bimetallic Ni-Pt showed higher activity and selectivity due to the presence of electron rich surface metallic Pt stabilized by Ni having lower ionization potential compared with Pt.

Simultaneous glycerol dehydration and in situ hydrogenolysis over Cu-Al oxide under an inert atmosphere - Mane, Rasika B.; Rode, Chandrashekhar V. (Green Chemistry, 2012)
Among various catalysts screened, the Cu-Al oxide catalyst, prepared by a co-precipitation method, exhibited excellent activity for simultaneous glycerol dehydration and its hydrogenolysis without external hydrogen. Detailed characterization by XRD, XPS, HR-TEM, TPR, etc., showed evidence of Cu2+ in the form of CuO and CuAl2O4, along with Cu-0 and Cu1+ species, which are responsible for their multifunctional roles in glycerol APR, dehydration and hydrogenolysis reactions under inert conditions. This catalyst also presented consistent activity for a duration of 400 h for autogeneous hydrogenolysis of refined glycerol with 36% selectivity to 1,2-propanediol (1,2-PDO). Manipulating the temperature and feed flow rate conditions, meant that the selectivity to acetol and 1,2-PDO could be tailored as desired. Substantial enhancement in 1,2-PDO selectivity (75%) was achieved for an aqueous bio-glycerol feed over the same catalyst for 50 h of testing.

Surface species of supported ruthenium catalysts in selective hydrogenation of levulinic esters for bio-refinery application - Hengne, Amol M.; Biradar, Narayan S.; Rode, Chandrashekhar V. (Catalysis Letters, 2012)
Several supported noble metal catalysts were screened for the hydrogenation of methyl levulinate to gamma-valerolactone (GVL). Among these catalysts 5 % Ru/C showed the highest conversion of 95 % of methyl levulinate with 91 % selectivity to GVL. A detailed characterization was carried out using TPR, XRD, XPS and BET techniques. XPS studies revealed that higher extent of Ru-0 species in case of carbon supported Ru was responsible for its higher hydrogenation activity as compared to Ru on other supports. Effect of process parameters such as temperature, H-2 pressure, catalyst and substrate concentration and metal loading on methyl LA conversion and selectivity to GVL also has been studied. 5 % Ru/C catalyst was found to be stable up to five reuses.
Keywords: 5 % Ru/C; Biofeedstock; gamma-Valerolactone; H-2-TPR; Hydrogenation; Methyl levulinate; XPS

Single pot conversion of furfuryl alcohol to levulinic esters and gamma-valerolactone in the presence of sulfonic acid functionalized ILs and metal catalysts - Hengne, Amol M.; Kamble, Sumit B.; Rode, Chandrashekhar V. (Green Chemistry, 2013)
Ionic liquids functionalized with acidic anions, HSO4, ClSO3H, PTSA, TFA (MIm), HSO4 and TFA (NMP) were found to efficiently (99% conversion) catalyze the alcoholysis of furfuryl alcohol (FAL) in the presence of methanol, ethanol, n-butanol and isopropyl alcohol (IPA) to the corresponding levulinic acid esters under mild temperature (90-130 degrees C) conditions. The extended alkyl chain length of [MIm] using 1,4-butane sultone enhanced the Bronsted acidity of [BMIm-SH][HSO4] catalyst resulting into the highest selectivity of >95% to Me-LA. An increase in both temperature and catalyst concentration increased the furfuryl alcohol conversion and selectivity to levulinate esters. In contrast, an increase in the substrate concentration from 5 to 15% caused a decrease in Me-LA selectivity due to accumulation of intermediate ethers of furfuryl alcohol. Using a combination of [BMIm-SH][HSO4] and 5% Ru/C catalyst, direct conversion of FAL to gamma-valerolactone (GVL) is shown for the first time. A complete conversion of FAL with the highest selectivity of 68% to GVL could be achieved under optimum conditions while higher Ru loading enhanced the GVL selectivity to 94% in the hydrogenation step of this tandem approach. Our catalyst system could be efficiently recycled five times retaining the original activity and selectivity levels.

Single-pot formation of THFAL via catalytic hydrogenation of FFR over Pd/MFI catalyst - Biradar, Narayan S.; Hengne, Amol M.; Birajdar, Shobha N.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Rode, Chandrashekhar V. (ACS Sustainable Chemistry & Engineering, 2014)
Furfural (FFR) was selectively hydrogenated in a single pot to tetrahydrofurfuryl alcohol (THFAL) over a Si MFI molecular sieve supported Pd catalyst. Studies on catalyst screening revealed that both the metal function and the support were critical for directing the selectivity to the ringhydrogenated product, THFAL. The structural feature of MFI as shown by XRD was completely retained in the used sample of the 3% Pd/MFI catalyst confirming its stability under reaction conditions. XRD, along with SEM characterization of the used samples, established retention of morphology of the structured silicate, suggesting a strong interaction between hexagonal porous silicate and Pd particles. The complete conversion of FFR with an enhanced selectivity of 95% to THFAL could be achieved by recycling the crude of the first hydrogenation experiment over the same 3% Pd/MFI catalyst.
Keywords: Biomass conversion; Hydrogenation; Pd/MFI; Recyclability; THFAL

Solvothermal synthesis of mesoporous manganese oxide with enhanced catalytic activity for veratryl alcohol oxidation - Jha, Ajay; Chandole, Tejansh; Pandya, Rajan; Roh, Hyun-Seog; Rode, Chandrashekhar V. (RSC Advances, 2014)
Catalyst activities of manganese and cobalt oxides prepared by solvothermal and co-precipitation methods were studied for veratryl alcohol oxidation. Manganese oxides showed higher activity performance than that of cobalt oxides irrespective of the method of preparation. The solvothermal method yielded mesoporous manganese oxide without using any template giving mixed phases of monoclinic Mn5O8 and hausmannite Mn3O4. The mesoporous manganese oxide exhibited excellent activity for liquid phase aerobic oxidation of veratryl alcohol under base free conditions, with 90% conversion and almost complete selectivity towards veratraldehyde. The detailed characterization results on morphology, size and composition of the prepared mesoporous manganese oxide obtained by XRD, XPS, H-2-TPR, N-2 adsorption-desorption isotherms, FESEM and HR-TEM techniques were used to understand the role of morphological and structural features in enhancement of the observed catalytic activity.

Surface synergism of an Ag-Ni/ZrO2 nanocomposite for the catalytic transfer hydrogenation of bio-derived platform molecules - Hengne, Amol M.; Malawadkar, Atul V.; Biradar, Narayan S.; Rode, Chandrashekhar V. (RSC Advances, 2014)
Levulinic acid was completely and selectively converted to GVL, in the presence of formic acid over an Ag-Ni/ZrO2 catalyst. The synergism between Ag and Ni in transfer hydrogenation eliminates the need for external hydrogen, making the process safer. The magnetic nature of the catalyst offers easy recovery for efficient recycling. This approach is standardized for the hydrogenation of several C-3-C-6 platform molecules in an aqueous medium.

Single pot transfer hydrogenation and aldolization of furfural over metal oxide catalysts - Biradar, Narayan S.; Hengne, Amol M.; Sakate, S. S.; Swami, R. K.; Rode, Chandrashekhar V. (Catalysis Letters, 2016)
One pot catalytic transfer hydrogenation (CTH) of furfural to furfuryl alcohol (FAL) by using hydrogen producing alcohols and simultaneous aldolization of carbonyl compounds produced during CTH, with furfural was achieved over non-noble metal oxides with bifunctional sites. Basic sites of MgO responsible for abstraction of proton showed complete conversion of furfural to give FAL and C8 monomer in a ratio of 3:1, respectively, the later altered to 1:1 by incorporating Al into MgO. Catalyst stability was established by its four cycles study. [GRAPHICS]
Keywords: Aldol; furfural; Furfuryl alcohol; Metal oxides; transfer hydrogenation

Single pot selective hydrogenation of furfural to 2-methylfuran over carbon supported iridium catalysts - Date, Nandan S.; Hengne, Amol M.; Huang, K-W.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Green Chemistry, 2018)
Various iridium supported carbon catalysts were prepared and screened for the direct hydrogenation of furfural (FFR) to 2-methyl furan (2-MF). Amongst these, 5% Ir/C showed excellent results with complete FFR conversion and highest selectivity of 95% to 2-MF at a very low H-2 pressure of 100 psig. Metallic (Ir degrees) and oxide (IrO2) phases of Ir catalyzed the first step hydrogenation involving FFR to FAL and subsequent hydrogenation to 2-MF, respectively. This was confirmed by XPS analysis and some control experiments. At a low temperature of 140 degrees C, almost equal selectivities of FAL (42%) and 2-MF (43%) were observed, while the higher temperature (220 degrees C) favored selective hydrodeoxygenation. At optimized temperature, 2-MF was formed selectively while higher pressure and higher catalyst loading favored ring hydrogenation of furfural rather than side chain hydrogenation. With the combination of several control experimental results and detailed catalyst characterization, a plausible reaction pathway has been proposed for the selective formation of 2-MF. The selectivity to various other products in FFR hydrogenation can be manipulated by tailoring the reaction conditions over the same catalyst.

Single-pot reductive rearrangement of furfural to cyclopentanone over silica-supported Pd catalysts - Date, Nandan S.; Kondawar, Sharda E.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (ACS Omega, 2018)
Direct one-pot hydrogenation of furfural (FFR) to cyclopentanone (CPO) was investigated over different silica-supported Pd catalysts. Among these, 4% Pd on fumed silica (4%Pd/f-SiO2) showed remarkable results, achieving almost 98% furfural (FFR) conversion with similar to 89% selectivity and 87% yield to cyclopentanone at 165 degrees C and 500 psig H-2 pressure. More interestingly, the fumed-silica-supported catalyst tuned the selectivity toward the rearrangement product, i.e, cyclopentanone, whereas all of the other supports were found to give ring hydrogenation as well as side chain hydrogenation products due to their parent Bronsted acidity and specific support properties. X-ray diffraction data revealed the presence of different phases of the face-centered cubic lattice of metallic Pd along with lowest crystallite size of 15.6 nm in the case of the silica-supported Pd catalyst. However, Pd particle size was found to be in the range of 5-13 nm with even dispersion over the silica support, confirmed by high-resolution transmission electron microscopy analysis. While studying the effect of reaction parameters, it was observed that lower temperature gave low furfural conversion of 58% with only 51% CPO selectivity.. Similarly, higher H-2 pressure lowered CPO selectivity with subsequent increase in 2-methyl furan and ring hydrogenation product 2-methyl furan and 2-methyl tetrahydrofuran. Thus, as per the requirement, the product selectivity can be tuned by varying the type of support and/or the reaction parameters suitably. With the help of several control experiments and the characterization data, a plausible reaction pathway was proposed for the selective formation of cyclopentanone.

Steering the ester and gamma-valerolactone selectivities in levulinic acid hydrogenation - Kasar, Gayatri B.; Date, Nandan S.; Bhosale, P. N.; Rode, Chandrashekhar V. (Energy Fuels, 2018)
Both alkyl esters and γ-valerolactone (GVL) derived from levulinic acid (LA) have applications as renewable transportation fuel/fuel additives. Non-noble metal cobalt supported on La2O3 catalyst was developed for efficient cascade LA hydrogenation to GVL via esterification. LA hydrogenation in methanol alone yielded methyl levulinate (MeLA) as a major product along with 43% of GVL. Interestingly, hydrogenation in water gave almost complete selectivity to GVL; nevertheless, it was associated with significant metal leaching. Suppression of metal leaching and enhancement in selectivity to GVL could be achieved by a methanol/water (95:5) solvent system. XRD analysis of La2O3-supported catalysts evidenced the characteristic peaks of a mixture of La2O3 and La(OH)3 phases. Basicity, as well as acidity, of the catalyst as determined by CO2 and NH3 TPD was due to these La2O3, Co–La, and La(OH)3 phases which played an important role in directing the product selectivity in levulinic acid hydrogenation. At the low temperature of 160 °C, almost equal selectivities of MeLA (47%) and GVL (43%) were observed, while higher temperature (200 °C) favored further hydrogenation of MeLA to GVL (75%). Similarly, with an increase in reaction time to 9 h, the GVL selectivity achieved was as high as 80%. The selectivity to MeLA and GVL in LA hydrogenation over Co/La2O3 catalyst can be altered by suitably adjusting the reaction conditions.

Synthesis of diesel additives from fructose over PWA/SBA-15 catalyst - Patil, Chetana R. (Fuel, 2018)
A series of composites of phosphotungstic acid (PWA) H3PW12O40 with SBA-15 were prepared by varying PWA amount from 5% to 30% by one-step sol-gel hydrothermal as well as by impregnation methods. Successful incorporation of PWA into the SBA-15 framework by sol-gel method was confirmed by 31P NMR in which a shifting of the peak due to tetrahedral ‘P’ atom of PWA from −14.32 and −14.49 ppm was observed. The composites exhibited both Brønsted and Lewis acidity, large and well distributed three dimensional interconnected pores with high surface areas exhibiting excellent activity for one pot synthesis of 5-(hydroxymethyl) furfural (5-HMF) and 5-(ethoxymethyl) furfural (EMF) from fructose. The minimum loading of 5% of PWA in SBA-15, gave 78% fructose conversion with the highest yield of 70% towards 5-HMF. Increase in PWA loading up to 20% resulted in the enhanced fructose conversion of 95% accompanied by further etherification of 5-HMF to 67 and 12% yield towards EMF and ethyl levulinate (EL), respectively. Increasing the % of PWA in SBA-15 matrix resulted in increase in the acidity of the composites giving the yield trend as 5-HMF < EMF < EL. Catalyst prepared by sol-gel method showed excellent recyclability up to 3 reuses
Keywords: 5-(Ethoxymethyl) furfural; 5-(Hydroxymethyl) furfural; Phosphotungstic acid; SBA-15

Single-pot alcoholysis of furfuryl alcohol to alkyl levulinates using heterogenized p-TSA catalyst** - Patil, Chetana R.; Kamble, Sanjay P.; Rode, Chandrashekhar V. (ChemistrySelect, 2021)
Synthesis of levulinate esters which are known to be excellent sustainable fuel additives, was achieved by alcoholysis of furfuryl alcohol over strong solid acid catalyst, prepared by copolymerization of p-toluenesulfonic acid with paraformaldehyde. Our catalyst possessed Bronsted acidity (3 mmol/g) with an excellent stability up to 220 degrees C. XPS, FT-IR and Pyridine-IR along with microanalysis studies confirmed the presence of terminal -SO3H functional groups responsible for Bronsted acidity in the catalyst. The catalyst was found to efficiently catalyze the alcoholysis of furfuryl alcohol to give alkyl levulinates under mild reaction conditions. The complete conversion of furfuryl alcohol with 96 % and 97 % selectivities to ethyl and butyl levulinates could be achieved using ethanol and butanol, respectively. Detailed study on effect of various reaction parameters like catalyst loading, reaction time and reaction temperature on conversion and product distribution was also carried out for the ethanolysis of furfuryl alcohol to ethyl levulinate. The catalyst could be easily recovered and recycled for five times successfully, with no loss in its original activity.
Keywords: Biomass; ethyl levulinate; Fuel additive; Furfuryl alcohol; heterogeneous catalysis

Solvent free, environment benign synthesis of 1,4-dihydropyridines and polyhydroquinolines by using heterogeneous Zn/MCM-41 catalyst - Dhengale, Shankar D.; Naik, Vaibhav M.; Kolekar, Govind B.; Rode, Chandrashekhar V.; Anbhule, Prashant V. (Research on Chemical Intermediates, 2021)
Heterogeneous catalysis has been utilized in number of efficient reactions with higher selectivity of the product, more stable, reusable and easy for separation as compared to homogeneous catalysts. Generally, heterogeneous catalysts are prepared by using mesoporous materials, microporous materials, metal oxides and metal organic framework. The mesoporous materials have small particle size and high surface area as compared to the microporous materials. The adsorbent mesoporous materials have highly efficient for the therapeutic applications in chemistry hence it has best as compared to other heterogeneous materials. Herein, we have reported synthesis of 1,4-dihydropyridines and polyhydroquinolines at solvent free and environmental benign condition in the presence of Zn/MCM-41 catalyst. The present protocol gives excellent yield (89-96%) of the product within short reaction time by easy work up procedure and no need of further purification of product. The catalyst was characterized by XRD diffractometer, SEM, EDAX, TGA-DTA, BET surface area analysis and FT-IR Spectroscopy. The synthesized organic compounds were characterized by FT-IR, H-1 NMR, C-13 NMR, LC-MS spectrometry.
Keywords: High activity; High selectivity; mesoporous materials; microporous materials; Reusability of catalyst